Parallel processing of cognitive and physical demands in left and right prefrontal cortices during smartphone use while walking. - Naoyuki Takeuchi; Takayuki Mori; Yoshimi Suzukamo; Naofumi Tanaka; Shin-Ichi Izumi; Takeuchi, Naoyuki; Mori, Takayuki; Suzukamo, Yoshimi; Tanaka, Naofumi; Izumi, Shin-Ichi (BMC Neuroscience, 2016)
Background: Smartphone use while walking is becoming a public concern owing to an increased risk of falling that can result from cognitive-motor interference. We evaluated prefrontal cortex (PFC) activity in participants playing a smartphone game while walking, in order to elucidate the role of the PFC in the allocation of attention between physical and cognitive demands. Sixteen young and 15 older adults participated in this study. Participants were instructed to perform a touch number-selecting game on a smartphone while walking. The numbers of correct and mistake responses were analyzed as a measure of cognitive performance. Linear trunk accelerations were measured by another smartphone and analyzed for step time and acceleration magnitude as an assay of gait performance. PFC activity during the task was measured using a wearable 16-channel near-infrared spectroscopy system.Results: Smartphone game playing while walking decreased the cognitive and gait performances compared with performances of single-task condition in older group more than in young group. There was no difference in PFC activation during smartphone use while walking between young and older groups, but age appeared to mediate correlation magnitude between PFC activation and changes in performance. In young adults, multiple regression analysis revealed an association of the right PFC with a reduction in acceleration magnitude (β = 0.581, p = 0.023), and an association of the left PFC with an increase in game-playing mistakes (β = -0.556, p = 0.032) during smartphone use while walking. In older adults, multiple regression analysis revealed an association of the middle PFC with a prolongation of step time (β = -0.550, p = 0.042) and of the left PFC with a reduction in acceleration magnitude (β = -0.648, p = 0.012).Conclusion: In young adults, the left PFC inhibited inappropriate action and the right PFC stabilized gait performance. In older adults, a less-lateralized PFC activity pattern suppressed the deterioration of gait performance, but this resulted in impairment on a simultaneous cognitive task. These results suggest that lateralization of motor and cognitive tasks aids in efficient task completion during a complex action such as using a smartphone while walking.